Evaluating the implementation of Check & Connect in various school settings: Is intervention fidelity necessarily associated with positive outcomes?. (June 2018) - Goulet, Mélissa; Archambault, Isabelle; Janosz, Michel; Christenson, Sandra L.
Highlights: Implementation fidelity is associated to Check & Connect's outcomes. Program components' intervention fidelity is differentially associated with outcomes. Implementation site and intervention context help understand these differences. Abstract: There are numerous school dropout prevention programs. However, few of them have undergone a rigorous implementation evaluation to understand their effects. This research presents two studies that evaluated the intervention fidelity and differential effects of Check & Connect (C&C), a targeted school dropout prevention program aimed at promoting student engagement and achievement. A total of 145 elementary school students (Study 1) and 200 secondary school students (Study 2) from two French-Canadian school boards (regional districts grouping elementary and secondary schools) received the C&C intervention for two years. In both studies, a clinical monitoring form was used to compare the intervention fidelity of each program component and active ingredient with what was initially planned. The relation between intervention fidelity and the effects of C&C on student engagement and achievement was analyzed using multiple linear regressions. Overall, the results show that intervention fidelity varies across elementary and secondary schools from one component to another and from one site to another. Furthermore, the association between the fidelity of each component and positive outcomes varies, depending on the implementation site. This evaluation supports the relevance of every component of C&C to favor engagement and academic achievement among at-risk elementary and secondary school students, while suggesting that the importance of certain program components may vary, depending on contextual influences on implementation and outcomes.